Design of SiO2-TiO2-P(AM-DMC) cationic composite flocculant and optimization of the flocculation process using response surface methodology. Issue 8 (14th June 2021) - Chao, Li; Wang, Haiwang; Wei, Xinfang; Li, Jinlong; Ji, Cheng; Qi, Xiwei
Abstract: At present, the polymer flocculation technology has been widely used in the treatment of oil sand tailings. However, the current composite flocculant still has the problems of low flocculation efficiency and serious secondary pollution after using. In this article, cationic composite flocculant SiO2 -TiO2 -P(AM-DMC) with self-degrading characteristics was prepared by the surface photoinitiated polymerization technique. Above all, in order to study the synthesis process of SiO2 -TiO2 -P(AM-DMC), cationic composite flocculant was characterized by FTIR, TG, TEM, XPS, etc. Furthermore, the central composite design (CCD) and response surface methodology (RSM) were used to optimize the preparation parameters of the cationic composite flocculant. And the optimization results of preparation parameters of cationic composite flocculant showed that the optimal preparation parameters of SiO2 -TiO2 -P(AM-DMC) were as follows: m DMC : m AM = 5, monomer concentration was 35% and reaction time was 100 min. Ultimately, the flocculation parameters of SiO2 -TiO2 -P(AM-DMC) were optimized by CCD and RSM. Moreover, the optimization results of flocculation parameters of cationic composite flocculant showed that the optimal flocculation parameters of SiO2 -TiO2 -P(AM-DMC) were as follows: pH = 5, flocculant dosage was 30 ppm, kaolin concentration was 1.36%. In summary, this work had greatly enriched the knowledge of oil sand tailings treatment, and had the extremely important reference significance for realizing the parameter regulation of high-efficiency flocculation of oil sand tailings. Graphical Abstract: